Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia - Salsabillah, Ananda; Gultom, Selfi Afriani; Napitupulu, Ilham Hidayah; Safrida, Eli; Nofianna, Siti Asnida (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
This research aims to analyze the effect of profitability, leverage and company size on firm value in energy sector companies listed on the Indonesia Stock Exchange. The Dependent Variable used in this study is Company Value, while the Independent Variables used are Profitability, Leverage, and Company Size. The type of data used is primary data. The sampling technique in this study was purposive sampling method. The sample in this study amounted to 20 companies and 100 observation data. The data collection technique used in this research is using documentation techniques. Data is collected based on annual reports and audited financial reports of energy sector companies for the period 2018 – 2022 which can be accessed through the official website of the Indonesia Stock Exchange. The data was processed and analyzed using multiple linear regression analysis techniques with SPSS software version 25. The t statistical test results show that the profitability ratio has an effect on firm value, with a significance level of 0.000. Leverage ratio has no effect on firm value, with a significance level of 0.05. The firm size ratio has no effect on firm value, with a significance level of 0.05.